Uncovering The Barriers and Business Impacts of E-Commerce Non-Adoption Among SMEs: A TOE Framework Perspective - Religia, Yoga; Ramawati, Yussi; Said, Jamaliah (Applied Information System and Management (AISM), 2025)
This study investigates barriers in technology, organization, and environment that prevent Indonesian SMEs from adopting e-commerce and examines their effects on business sustainability. Using the TOE framework, this research adopts a quantitative cross-sectional method, with data from 320 SMEs analyzed using PLS-SEM. Results reveal that technological and environmental barriers significantly hinder e-commerce adoption, negatively affecting sustainability, while organizational barriers have no significant impact. These findings highlight the need for targeted interventions to address technological and environmental challenges. The study provides valuable insights for policymakers to foster supportive environments, enhance SME competitiveness, and promote digital inclusion. By addressing these barriers, SMEs can access digital markets more effectively, improve performance, and contribute to economic growth. This research underscores the importance of policies supporting SME growth and digital transformation, offering guidance to improve e-commerce adoption and business sustainability in the digital era.